Evolution of the RECQ family of helicases. A Drosophila homolog, dmblm, is similar to the human bloom syndrome gene. - Kusano, K.; Berres, M.E.; Engels, W.R. (Genetics, 1999)
Several eukaryotic homologs of the Escherichia coli RecQ DNA helicase have been found. These include the human BLM gene, whose mutation results in Bloom syndrome, and the human WRN gene, whose mutation leads to Werner syndrome resembling premature aging. We cloned a Drosophila melanogaster homolog of the RECQ helicase family, Dmblm (Drosophila melanogaster Bloom), which encodes a putative 1487-amino-acid protein. Phylogenetic and dot plot analyses for the RECQ family, including 10 eukaryotic and 3 prokaryotic genes, indicate Dmblm is most closely related to the Homo sapiens BLM gene, suggesting functional similarity. Also, we found that Dmblm cDNA partially rescued the sensitivity to methyl methanesulfonate of Saccharomyces cerevisiae sgs1 mutant, demonstrating the presence of a functional similarity between Dmblm and SGS1. Our analyses identify four possible subfamilies in the RECQ family: (1) the BLM subgroup (H. sapiens Bloom, D. melanogaster Dmblm, and Caenorhabditis elegans T04A11.6); (2) the yeast RECQ subgroup (S. cerevisiae SGS1 and Schizosaccharomyces pombe rqh1/rad12); (3) the RECQL/Q1 subgroup (H. sapiens RECQL/Q1 and C. elegans K02F3.1); and (4) the WRN subgroup (H. sapiens Werner and C. elegans F18C5.2). This result may indicate that metazoans hold at least three RECQ genes, each of which may have a different function, and that multiple RECQ genes diverged with the generation of multicellular organisms. We propose that invertebrates such as nematodes and insects are useful as model systems of human genetic diseases.